IMPROVING THE ECONOMICREGULATIONOFWOMEN’S EMPLOYMENT (Uzbekistan Open Conference, 2025)
the article explores the employment problems of women living in working-age rural areas. From the laws of the formation of employment with Labor, directions have been proposed to improve the forms of ownership in the village, small and medium-sized entrepreneurship among rural women, the development of workmanship again.